La place des inégalités sociales d'apprentissage comme objet et cadre d'analyse dans les mémoires de master - Claire Benveniste (Université de Provence, 2018)
By focusing on the themes and bibliographies of master MEEF dissertations, this article examines the initial training of primary school teachers in terms of reducing social inequalities at school. We first analyze the place of issues related to school inequalities in the official discourse on the training and the place of research during the initial training. The implementation of these national guidelines in two ESPE is then studied via the statistical analysis of the themes and bibliographies of 115 MEEF first-degree dissertations. The results show on the one hand that trainee teachers prefer rather didactic and psychological approaches, little crossed to a sociological questioning on the reduction of inequalities, and on the other hand, training for or through research is not self-evident despite the introduction of devices that claim to do so.